Imperialism and International Law: The Case of the Northern Malay States in the 19th Century - Jeshurun, Chandran (Journal of Malaysian and Comparative Law, 2018)
Book Review of Piracy, Paramountch and Protectorates by Alfred P. Rubin, Penerbit Universiti Malaya (1974)